Outcome measures for adult and pediatric hemophilia patients with inhibitors. (25th April 2017) - Hermans, Cedric; Auerswald, Günter; Benson, Gary; Dolan, Gerry; Duffy, Anne; Jiménez‐Yuste, Victor; Ljung, Rolf; Morfini, Massimo; Lambert, Thierry; Osooli, Mehdi; Zupančić Šalek, Silva
Abstract: Recent advancements in almost all aspects of hemophilia treatment have vastly improved patient care and management, and new and emerging treatments hold the promise of further progress. However, there remains a scarcity of data on long‐term outcomes in hemophilia, particularly among those patients with inhibitors, for whom no validated outcome assessment tools are currently available. At the 15 th Zürich Haemophilia Forum, an expert panel reviewed the most important outcome measures in inhibitor patients and considered the challenges associated with assessing outcomes in this population. A framework for outcome assessment in inhibitor patients incorporates traditional hemophilia outcome measures, such as bleed frequency and mortality, alongside measures of health, functioning, disability, social participation, quality of life, and economic considerations. It is important to remember that inhibitor patients differ in their clinical needs, perspectives, and priorities according to age, inhibitor status, degree of joint disease, and activity levels; as a result, the relative importance of different outcome measures will change throughout an inhibitor patient's life. Challenges inherent in measuring long‐term outcomes in inhibitor patients include the small number of known patients, the subjective nature of many outcome assessment tools, and the risk of overburdening patients with repeated requests to complete questionnaires or participate in studies. Therefore, there is an urgent need to reach consensus on the most important and appropriate assessment tools for measuring outcomes in this population. These tools should ideally be standardized, easily applied, and internationally applicable in order to collect and generate quality outcome data.